The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jpc.13308
|View full text |Cite
|
Sign up to set email alerts
|

Association of cord blood vitamin D with early childhood growth and neurodevelopment

Abstract: Cord blood vitamin D was modestly, positively associated with language development in early childhood in our sample, although the magnitude of the association was small. Randomised controlled trials are needed to confirm a causal association and establish the potential clinical significance of the relationship between vitamin D status and language development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 28 publications
4
56
2
Order By: Relevance
“…The findings are also similar to those from a cohort study in India, where vitamin D status in early childhood was not associated with the gross motor functioning among school aged children [36]. Studies that have examined the association between cord blood vitamin D concentrations and neurodevelopment measured in early and middle childhood have shown mixed results [37,38]. Furthermore, studies that have examined the associations between vitamin D Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The findings are also similar to those from a cohort study in India, where vitamin D status in early childhood was not associated with the gross motor functioning among school aged children [36]. Studies that have examined the association between cord blood vitamin D concentrations and neurodevelopment measured in early and middle childhood have shown mixed results [37,38]. Furthermore, studies that have examined the associations between vitamin D Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The shaded area spans the 95% confidence interval of this association deficiency during pregnancy and neurodevelopment during early and middle childhood have also shown inconsistent results [7][8][9][10][11][12]39]. Three studies found an association between pregnancy vitamin D status and neurodevelopment outcomes in children before 4 years of age [8,11,38], while one study found marginal associations with language scores at 10 years of age [10]. The inconsistencies are likely due to differences in the populations, the timing of vitamin D assessment during pregnancy, the use of different cut-offs for vitamin D deficiency, age of the child at developmental assessments, and the way potential confounders were handled.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies did not find any association between prenatal vitamin D levels and global IQ or cognitive development at preschool [69][70][71][72] and school age [73,74]. However, Keim et al [75] reported a positive association between both maternal and cord blood 25(OH)D concentration and IQ at age 7, but the effect estimates were very small.…”
Section: Global Intelligence Quotient (Iq) or Cognitive Developmentmentioning
confidence: 91%
“…Two studies reported increased psychomotor scores at age 14 months [51] and at 30 months [74] associated with higher maternal vitamin D concentrations in pregnancy. However, 4 studies did not find any association [69,71,72,75]. Furthermore, Zhu et al [76] found an inverted-U-shaped relation between neonatal vitamin D status and psychomotor score in toddlers.…”
Section: Psychomotor Outcomesmentioning
confidence: 98%
“…There is considerable heterogeneity in observational studies, including study size, maternal gestation at assessment and population demographics, but when considered together, these studies would suggest that foetal size is only affected at the lowest levels of maternal 25(OH)D and the relationship is non-linear. Indeed, studies which have considered 25(OH)D as a continuous variable have not typically identified a significant relationship between maternal 25(OH) D and offspring birth weight or length [73,75,[88][89][90][91][92][93][94][95][96][97]. In contrast, dichotomisation of maternal serum 25(OH)D to compare two or more groups identified significantly lower birth weight in babies born to mothers who were classed as VDD when thresholds between 25 and 37.5 nmol/l were used to define VDD, but not in studies that used a higher serum 25(OH)D to define VDD [75,89,90,[98][99][100][101][102][103].…”
Section: Birth Anthropometry and Childhood Growthmentioning
confidence: 99%